2015
DOI: 10.1007/s11199-015-0530-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Size in Mate Selection among African American Young Adults

Abstract: A profusion of studies have demonstrated that body size is a major factor in mate selection for both men and women. The particular role played by weight, however, has been subject to some debate, particularly with respect to the types of body sizes deemed most attractive, and scholars have questioned the degree to which body size preferences are constant across groups. In this paper, we drew from two perspectives on this issue, Sexual Strategies Theory and what we termed the cultural variability perspective, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Perhaps, this relationship lies in the need for singles to take care of their physical appearance in order to be able to find a serious partner in the future. This reasoning is consistent with those works that have evidenced the relationship between overweight and casual sexual encounters to the detriment of serious romantic relationships (more common among those with normal weight) that end up leading to a change in the marital status of individuals (Frederick and Jenkins, 2015;Granberg et al, 2015). Besides, our findings on the implications that residing in urban areas has on BMI≥25 contribute to reduce the controversy about the direction of urbanrural gaps in overweight (Sjoberg et al, 2012;Emamian et al, 2017;Rood y Sharma, 2017;Thapa et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps, this relationship lies in the need for singles to take care of their physical appearance in order to be able to find a serious partner in the future. This reasoning is consistent with those works that have evidenced the relationship between overweight and casual sexual encounters to the detriment of serious romantic relationships (more common among those with normal weight) that end up leading to a change in the marital status of individuals (Frederick and Jenkins, 2015;Granberg et al, 2015). Besides, our findings on the implications that residing in urban areas has on BMI≥25 contribute to reduce the controversy about the direction of urbanrural gaps in overweight (Sjoberg et al, 2012;Emamian et al, 2017;Rood y Sharma, 2017;Thapa et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Participants viewed nine figures and chose which figure most accurately depicted their own body. Although these figures are not explicitly African American in appearance, they have been widely used in studies with African American respondents and have demonstrated validity as a measure of weight (Bulik et al, 2001; Granberg, Simons & Simons, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We use self-assessments of physique rather than a measure such as BMI because the latter does not necessarily capture a person’s overall physique, muscle tone, distribution of fat, or appearance (Deurenberg & Deurenberg-Yap, 2003; Granberg, Simons & Simons, 2015). For instance, an individual could have a wide frame or more muscle, resulting in a high BMI, when they are not overweight or carrying too much fat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations